MicroRNA-140-5p inhibits cell proliferation, migration and promotes cell apoptosis in gastric cancer through the negative regulation of THY1-mediated Notch signaling. Issue 7 (23rd July 2019) - Wu, Kun; Zou, Jun; Lin, Chao; Jie, Zhi-Gang
Abstract : Studies have highlighted the importance of microRNAs (miRs) in the development of various cancers, including gastric cancer (GC), a commonly occurring malignancy, accompanied by high recurrence and metastasis rate. The aim of the current study was to investigate the role of miR-140-5p in GC. Microarray expression profiles were initially employed to screen the differentially expressed gene related to GC, and the miR regulating the gene was predicted accordingly. The data obtained indicated that thymus cell antigen 1 ( THY1 ) was differentially expressed in GC and confirmed to be a target gene of miR-140-5p. Poorly expressed miR-140-5p and highly expressed THY1 were observed in the GC tissues. SGC-7901 cells were treated with miR-140-5p mimic/inhibitor, siRNA against THY1 and siRNA against Notch1 in order to determine their regulatory roles in GC cell activities. The relationship of miR-140-5p, THY1 and the Notch signaling pathway was subsequently identified. Moreover, cell proliferation, migration, invasion and apoptosis were determined using 3-(4, 5-dimethylthiazol-2-yl)-5(3-carboxymethonyphenol)-2-(4-sulfophenyl)-2H-tetrazolium (MTS), wound-healing, transwell assay and flow cytometry, respectively. The overexpression of miR-140-5p and silencing of THY1 resulted in a diminished expression of the Notch signaling pathway-related proteins, as well as inhibited proliferation, migration and invasion of GC cells, enhanced expression of pro-apoptotic proteins in addition to elevated apoptosis rate. Taken together, the present study suggests that miR-140-5p directly targets and negatively regulates THY1 expression and inhibits activation of the Notch signaling pathway, whereby the up-regulation of miR-140-5p inhibits development of GC, highlighting the promise of miR-140-5p as a potential target for GC treatment.